Prioritizing Promotion Strategies using Analytic Hierarchy Process (AHP) Study - Utomo, Bagus Susanto; Attamimy, Helmy Bachtiar (Indonesian Journal of Global Health Research, 2024)
Surabaya Medical Service Hospital has problems in implementing the hospital promotion program which is less effective, which is only known and felt by 56% of the total respondents who use services at Surabaya Medical Service Hospital. The aim of this research is to determine the priority order of available alternative strategies using the Analytic Hierarchy Process to increase the effectiveness of promotional program strategies at the Surabaya Medical Service Hospital. This research uses a cross sectional method with a mixed method approach which combines qualitative and quantitative approaches. This research sample consists of two categories, visiting patients and marketing management at the Surabaya Medical Service Hospital. The research was conducted in the period November – December 2023. Research data, both qualitative and quantitative research are processed and then analyzed using descriptive analysis. The analytic hierarchy process procedure consists of 2 parts: prioritizing criteria factors that influence alternative choices and assessing through scoring and weighting to produce score levels. The results of this research show the identification of internal factors including the management of tangible assets and intangible assets. In the customer factor, it was found that the main references regarding hospital services came from family or neighbors. The promotional strategy determined by the Surabaya Medical Service Hospital is by implementing a promotion mix through direct marketing, advertising, public relations and personal selling. The results of weighting the promotional strategy criteria for the Surabaya Medical Service Hospital were availability of key informants (0.586), reach (0.228), costs (0.101), completeness of information (0.085). Then, the alternative weighting for RS SMS promotional strategies is Personal selling (0.4018), Direct marketing (0.3046), public relations (0.1614) and Advertising (0.1322). The sequence of priority promotional strategies that can be implemented by the Surabaya Medical Service Hospital are, respectively, personal selling, direct marketing, public relations and advertising.